Airliner conceptual designs for the application of alternative fuels - Chan, Joseph Lok Chun; Sun, Yicheng; Smith, Howard (American Institute of Aeronautics and Astronautics (AIAA), 2026)
This paper investigates the application of alternative fuels in tube-and-wing aircraft configurations. Potential alternative fuel choices include biofuel, liquid hydrogen, liquefied natural gas, and ammonia. A comprehensive mission range starting from 2000 nautical miles to 8500 nautical miles is explored, designed, and analyzed using GENUS, an in-house built multidisciplinary design analysis and optimization platform. This paper aims to give a comprehensive study of different alternative fuel options and capacity combinations over different mission ranges. The different gradients of these trends demonstrate the additional benefits of using alternative fuels. The objectives of this study are 1) to determine how different fuel properties affect the designs and performance of aircraft and 2) to quantify the reduction of greenhouse gas (GHG) emissions by utilizing alternative fuel. The results show cryogenic fuel, which requires fuselage fuel tanks and/or external fuel tanks, will noticeably increase energy consumption due to drag and weight penalties. Yet, the high specific energy density properties of liquid hydrogen (LH2) will offset the penalties and result in a reduction in specific energy consumption (MJ/pax/nm), especially in a high-capacity, long-range mission. A 20.8 and 13.7% reduction in specific energy consumption is calculated between the use of kerosene-based jet fuel and LX2 for a 400 and 800 pax design with an 8500 nm mission range, respectively. In addition, the use of LX2 and biofuel can significantly reduce life cycle GHG emissions if the fuel is produced through sustainable pathways.
Keywords: 40 Engineering; 4001 Aerospace Engineering; 7 Affordable and Clean Energy; 13 Climate Action; Aerospace & Aeronautics